Breakthrough COVID‐19 cases despite prophylaxis with 150 mg of tixagevimab and 150 mg of cilgavimab in kidney transplant recipients. Issue 11 (30th June 2022) - Benotmane, Ilies; Velay, Aurélie; Gautier‐Vargas, Gabriela; Olagne, Jérôme; Obrecht, Augustin; Cognard, Noëlle; Heibel, Françoise; Braun‐Parvez, Laura; Keller, Nicolas; Martzloff, Jonas; Perrin, Peggy; Pszczolinski, Romain; et al.
Abstract: The cilgavimab−tixagevimab combination retains a partial in vitro neutralizing activity against the current SARS‐CoV‐2 variants of concern (omicron BA.1, BA.1.1, and BA.2). Here, we examined whether preexposure prophylaxis with cilgavimab−tixagevimab can effectively protect kidney transplant recipients (KTRs) against the omicron variant. Of the 416 KTRs who received intramuscular prophylactic injections of 150 mg tixagevimab and 150 mg cilgavimab, 39 (9.4%) developed COVID‐19. With the exception of one case, all patients were symptomatic. Hospitalization and admission to an intensive care unit were required for 14 (35.9%) and three patients (7.7%), respectively. Two KTRs died of COVID‐19‐related acute respiratory distress syndrome. SARS‐CoV‐2 sequencing was carried out in 15 cases (BA.1, n = 5; BA.1.1, n = 9; BA.2, n = 1). Viral neutralizing activity of the serum against the BA.1 variant was negative in the 12 tested patients, suggesting that this prophylactic strategy does not provide sufficient protection against this variant of concern. In summary, preexposure prophylaxis with cilgavimab−tixagevimab at the dose of 150 mg of each antibody does not adequately protect KTRs against omicron. Further clarification of the optimal dosing can assist in our understanding of how best to harness its protective potential. Abstract : Breakthrough of COVID‐19 cases despite prophylaxis with cilgavimab‐tixagevimab in kidney transplant recipients confirm the recent FDA recommendations to increase cilgavimab‐tixagevimab dosing.